Inquiry-based olericulture seed cultivation program to increase industrial agricultural insight and student entrepreneurship spirit - Zhahrotun Nurroniah; Safina Aulia Sani; Rike Dwi Wulandari; Nadiah Putri Anggraeni; Nidya Nur Mashitoh; Lailatul Nuraini (University of Merdeka Malang, 2023)
Learning about insights into industrial agriculture and the entrepreneurship spirit should be instilled from an earlier to students so that they develop social interaction skills and a motivation to work in the future. This research aims to improve the understanding of industrial agriculture and the entrepreneurial spirit of Jomerto 02 Patrang Elementary School students through inquiry-based cultivation of olericulture seedlings. One of the plants that is easy to plant and has an expensive harvest is the olericulture plant. The method of service implementation used by the researchers is the Service Learning (SL) approach. The results of this study show that the teachers' recapitulation results were 97.5% and included in the very good category, and the students' recapitulation results of the three indicators were in the very good category. This is evidenced by the data of the results of the indicator of self-efficacy with 82.45%, the data of the percentage results of the indicator of need for achievement with 90.96% and the percentage result of the Riks Taking Propensity indicator is 92.34%. In other words, the efforts to improve the understanding of industrial agriculture and the entrepreneurial spirit of the students of SDN Jomerto 02 Patrang can be continued by the school.